2015
DOI: 10.1002/pc.23484
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermo-oxidative aging on vibration damping characteristics of conventional and graphene-based carbon fiber fabric composites

Abstract: The effect of thermo‐oxidative aging on the vibration damping characteristics of the conventional fabric composites reinforced by three‐dimensional (3D) and four‐directional (4Dir) braided preform and laminated plain woven fabric and the 3D‐4Dir braided graphene‐based carbon fiber composites was investigated. Specimens were isothermally aged at 140 °C for various periods of time up to 1,200 h. The results indicated that the thermo‐oxidative aging resulted in deterioration of the matrix and interface performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The micro-cracks provide additional paths for oxygen diffusion, thus accelerating the degradation rate. Many studies (Cao et al., 2018; da Silva et al., 2016; Fan et al., 2016; Mouzakis et al., 2014; Wang et al., 2017) have demonstrated that the deterioration of the fiber–matrix interface and consequent fiber debonding caused by thermal oxidation ageing had a significant influence on the failure mechanism of composites.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-cracks provide additional paths for oxygen diffusion, thus accelerating the degradation rate. Many studies (Cao et al., 2018; da Silva et al., 2016; Fan et al., 2016; Mouzakis et al., 2014; Wang et al., 2017) have demonstrated that the deterioration of the fiber–matrix interface and consequent fiber debonding caused by thermal oxidation ageing had a significant influence on the failure mechanism of composites.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fibers have been more and more widely used in the fields of aerospace and petrochemical and medical treatment (Sheehan et al, 1994;Park and Kim, 2010), owing to their unique stabilities, elastic moduli, strengths, stiffness, thermal conductivities, and lightweightness (Ruland, 1990;Keiji et al, 2004;Wu et al, 2010). Nevertheless, the high stiffness of carbonfiber composite materials could lead to relatively low damping performance, in which case original cracks will be quickly propagated under the actions of periodic loads and external shocks, eventually resulting in vibration, fatigue, and failure (Khan et al, 2011;Fan et al, 2016). Hence, effective measures should be taken to enhance the damping properties of carbon fiber materials.…”
Section: Vibration and Noise Reduction Based On The Damping Propertymentioning
confidence: 99%
“…Fan et al . investigated the effects of 3Dim and 4Dir braiding preform and laminated plain woven fabric on the thermal oxidative stability of FRPMCs . The results showed that the retention rates of weight loss, bending properties, compression property, thermal conductivity, vibration performance, flexural property, shear strength, and impact property of the 3Dim braided composites were greater than those of the laminated composite.…”
Section: Impact Mechanism Of Temperature On Frpmcsmentioning
confidence: 99%